The Pandemic Visual Regime Visuality and Performativity in the Covid-19 Crisis - Ramírez Blanco, Julia; Spampinato, Francesco (punctum books, 2023)
The Covid-19 pandemic has been expressed in various ways through visuality and performance, and some of its more nuanced cultural implications have taken place in a realm that goes beyond words. Through the exploration of the visual culture produced during and in response to the Covid-19 pandemic, The Pandemic Visual Regime: Visuality and Performativity in the Covid-19 Crisis highlights the key role played by images in shaping our understanding of the epochal transformations our society is undergoing. This book argues that visuality and its relationships with the performative have played such a significant role in the Covid-19 pandemic that we can even speak of the emergence of a "pandemic visual regime," a new way of seeing and representing the world under this global emergency. Through an interdisciplinary framework, The Pandemic Visual Regime aims to answer an array of questions: In which ways have the effects of the pandemic been racialized, thereby reinforcing white supremacy? How are our responses to Covid-19 shaped by the Hollywood "outbreak narrative" of films such as Contagion? How has design responded to our new pandemic needs? How have infographics affected our perception? In which new ways have we come to inhabit private, public, and virtual space? Regarding the latter, what changes have there been in the forms of digital surveillance? On the other side of the spectrum, what forms has mutual aid taken and what have been our forms of relating with nature, both during lockdown and after lockdown was over? All these questions open the field to rethinking the visuality of our post-pandemic zeitgeist.